3D printing and additive manufacturing for customised design: unmanned vehicles - engine parts II - Lee, Weng Kit (2015)
Additive Manufacturing (AM) technology came about as a results of developments in a variety of different technology sectors. AM is referred to as a process which a components is build up using digital 3D design data in layers by depositing material. Additive manufacturing offers many strategic advantages, including increase in design freedom for building complex internal and external geometry part geometries, the ability to build functional parts in small lot sizes for end-user customisation as well as the ability to repair expensive parts for aerospace and other industries. In the industry of product design, 3D printing is used to print parts to examine is functionality, ergonomics and well as aesthetics. It allows the company to reduce its cost to produce prototype as well as time. Chassis of car can also be printed as a whole instead of the conventional method which requires welding or joining of several parts together. This increases the structural integrity and therefore are much stronger. In this project, drive shaft for a radio controlled car is fabricated using 3D printing. Taking the advantage of additive manufacturing, complex shapes and design has also been introduced into the re-design of the drive shaft. While 3D printing allows a greater freedom of design, each part requires design optimisation which may depend on the orientation of printing, the material used or the method of printing. The fabricated drive shaft will then undergo various testing that is adapted from standard automobile testing to simulate real operating conditions. The experimental results will also be verified with the simulation results that will be performed using ANSYS software.